2017
DOI: 10.1542/peds.2016-4040
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and Diagnosis of Tuberous Sclerosis Complex in Infants

Abstract: Infants with TSC can often be identified early, before the onset of neurologic sequelae, enabling earlier diagnosis, surveillance, and possibly disease-modifying treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 44 publications
7
81
0
5
Order By: Relevance
“…Age of onset ranged from day of birth to 22 months, with a median age of onset at 4 months (interquartile range = 4.56 months). Of those with seizures, 62.5% (20/32) had infantile spasms, a rate that is similar to previously published estimates [Davis et al, ]. Information regarding the presence of cortical tubers was present for 80% of the TSC sample ( n = 28).…”
Section: Methodssupporting
confidence: 86%
“…Age of onset ranged from day of birth to 22 months, with a median age of onset at 4 months (interquartile range = 4.56 months). Of those with seizures, 62.5% (20/32) had infantile spasms, a rate that is similar to previously published estimates [Davis et al, ]. Information regarding the presence of cortical tubers was present for 80% of the TSC sample ( n = 28).…”
Section: Methodssupporting
confidence: 86%
“…4,[11][12][13] We recognize that this study did not incorporate the neuroimaging findings for this cohort, which also may be a contributing factor to the cognitive decline in some of the participants. Our data suggest that there is a specific association between severity of epilepsy and comorbid conditions, including developmental delay, reported previously in retrospective and prospective series.…”
Section: Discussionmentioning
confidence: 99%
“…The studies collected clinical and genetic data, neuropsychological testing, serial magnetic resonance imaging (MRI) studies, and serial EEG studies, through age 3 years. Complete study protocol and design were reported previously . The study protocols were approved by the institutional review board at each site with direction from the leading regulatory core at Cincinnati Children's Hospital Medical Center.…”
Section: Methodsmentioning
confidence: 99%